SYNTHESIS AND CHARACTERIZATION OF 7-HYDROXY-4-METHYLCOUMARIN-CHITOSAN FILM AS FLUORESCENT MATERIAL - ZULQARNAEN (NIM : 10508105); Pembimbing 1 : Dr. Deana Wahyuningrum; Pembimbing 2 : Dr. V, MUHAMMAD
Fluorescent material has been developed for display technologies, lasers, or solar cells. Coumarin group of compounds in the solution is often used as a dye laser, lightening agents in detergents, or fluorescent markers. This study aims to make a film of chitosan-containing 7-hydroxy-4-methylcoumarin (7H4MC) that can undergo fluorescence. Used chitosan obtained from chitin isolated from skin of tiger prawns (Penaeus monodon) through the deproteination, demineralization, and deacetylation process. The yield of chitin and chitosan, respectively 10.66% and 23.83%. Obtained chitosan has a degree of deacetylation of 55.00% based on FTIR spectroscopy. Average molecular mass of chitosan was determined by the method of OstwaldÃ‚Â’s viskometri is 8.55 x 106 g/mol. Compound 7H4MC synthesized from resorcinol and ethyl acetoacetate and amberlyst-15 as catalyst based on Pechmann reaction with a yield of 90.01% and the melting point of 189-190oC. TLC test with the stationary phase silica gel 60 F254 (Merck) and the eluent n-hexane: ethyl acetate (3:2) gave the results of the stain with Rf = 0.46 which shows the synthesis of pure 7H4MC. IR spectrum of 7H4MC shows O-H absorption at ν = 3500 cm-1, =C-H at ν = 3113 cm-1, conjugated C=O at ν = 1671 cm-1, C=C at ν = 1607 cm-1, and symmetric deformation vibrations of the methyl group at ν = 1394 cm-1. Proton NMR spectrum (500 MHz, DMSO-d6) showed signals for six types of hydrogen, namely the chemical shift 2.34 (s, 3H), 6.10 (s, 1H), 6.69 (d, J = 2.34 Hz, 1H), 6.78 (dd, Ja = 2.36 Hz, Jb = 8.67 Hz, 1 H), 7.56 (d, J = 8.69 Hz, 1H), and 10.51 ppm (s, broad, 1H). Carbon-13 NMR spectrum (125 MHz, DMSO-d6) showed signals of the lactone carbonyl (161.17 ppm), eight aromatic/alkene carbon (160.31; 154.85; 153.52; 126.59; 112.87; 112.03; 110.27; 102.19 ppm), and one methyl carbon (18.12 ppm). IR, 1H-NMR, and 13C-NMR spectrums confirmed the structure of the corresponding 7H4MC synthetic products. Films of 7H4MC-chitosan prepared by solvent evaporation method in acetic acid 2% (v/v). Variation of 7H4MC content in each film was 0% (blank), 0.2%, 0.4%, 0.6%, and 0.8% (w/w). All films fluoresce under UV light with λ = 365 nm, except for the blank. UV-Vis spectroscopy 7H4MC in methanol showed λmax at 235 and 337 nm. The observed fluorescence is the fluorescence color of cyan. The exciting wavelength is 200, 235, 275, 337, and 365 nm. Cyan color fluorescence of the film with highest intensity is obtained at a concentration of 7-hydroxy-4-metilkumarin 0.2% with the exciting wavelength of 275 nm.